PENGGUNAAN BAHASA DALAM NARASI SINGKAT MEDIA SOSIAL MAHASISWA - Dian Mawaddah Naibaho; Fitri Yeni; Hanifah Rifqia Zain; Manja Amanda; Nabila Aufa Zahira; Farel Olva Zuve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social media has become the main communication space for students, influencing interaction patterns and language use, particularly in writing short narratives (captions). In practice, students tend to use non-standard language, such as slang and mixed with foreign languages, as a more relaxed and interactive communication strategy. This phenomenon is interesting to study because it has the potential to influence the effectiveness of message delivery and attitudes towards language politeness. This study aims to describe the use of slang in students' social media captions and analyze its influence on the attractiveness of messages and attitudes towards standard Indonesian. The study uses a descriptive quantitative approach with a survey method. Data were collected through an online questionnaire distributed to active social media users from various study programs. Data analysis was performed using descriptive statistics in the form of percentages. The results show that the majority of students are accustomed to writing captions and predominantly use slang, non-standard language, and a mixture of Indonesian and English. Most respondents believe that slang facilitates message delivery and increases the appeal of posts. Nevertheless, students still showed a positive attitude towards the importance of linguistic politeness and the use of standard Indonesian in formal and academic contexts. These findings indicate that language use in social media is contextual and adaptive, reflecting students' linguistic flexibility without shifting their awareness of linguistic norms.